William Cobbett's correspondence, 1800-1835 - Grande, J (2013)
The vast majority of William Cobbett’s personal letters have never been published. This thesis examines these manuscripts alongside the ‘open letter’ form that dominated his published writings, using correspondence to illuminate the hybrid and highly idiosyncratic form of Cobbett’s radicalism. It shows how he responded to continued persecution from the government through a series of innovative epistolary strategies, creating a popular journalism that incorporated many of the tropes usually associated with letter writing, including familiarity, authenticity, the spontaneity of speech and the domestic scene of reception. These became inseparable from the idealized presentation of Cobbett’s own radical and agrarian domestic life, and this thesis represents the first critical study to address the significance of Cobbett’s family in the physical production and imaginative world of his writings, drawing on many of the letters written by his seven children. Individual chapters concentrate on a series of episodes in Cobbett’s post-1800 career, including his friendship with William Windham, imprisonment in Newgate, exile in America, support for Queen Caroline and writings on the Captain Swing uprising. During these years, Cobbett’s correspondence helped to establish the modern newspaper leading article as an open letter to readers, although Cobbett’s are stamped with his own personal authority. However, while correspondence invested Cobbett’s journalism with a sense of situatedness unmatched in radical writing of the period, it also highlights some of the tensions within his political and pedagogical practice. By the 1820s, Cobbett’s correspondence bristles with the contradictions of wanting to recognize the individuality and difference of his readers’ lives, and at the same time pull them within the orbit of a very paternal political vision.